Primary aldosteronism: pharmacotherapy vs surgery vs embolization efficacy – systematic review and network meta-analysis of studies predominantly conducted in China - Li, Gang; Xu, Wenping; Li, Changjun; Hu, Peng; Qin, Siqin (Frontiers in Endocrinology, 2025)
BackgroundPrimary aldosteronism (PA) is one of major cause of resistant hypertension. This study compares the efficacy and safety of current treatments, including pharmacotherapy, adrenalectomy, and minimally invasive techniques, to guide clinical practice.MethodWe systematically searched Embase, PubMed, Cochrane, Web of Science, CNKI, Wanfang, and VIP from inception to August 13, 2024, for randomized controlled trials and cohort studies involving adult patients with PA and hypertension. Reporting quality of the included studies was assessed using the Cochrane Risk of Bias 2 tool for RCTs and the Newcastle-Ottawa Scale (NOS) for cohort studies. Data analysis was performed using R 4.3.3 and STATA 15.0.ResultsThis study included 17 articles involving 1,496 patients, of which 13 studies (76%) were conducted in China. Meta-analysis showed that for systolic blood pressure (SBP), unilateral total adrenalectomy and renal nerve denervation (TADR+RND) was most effective (WMD = -12.53, 95% Crl -15.18 to -9.90). For diastolic blood pressure (DBP), Partial adrenalectomy (PADR) (WMD = -9.31, 95% Crl -12.97 to -5.68). PADR also maintained serum potassium levels effectively (0.64, 95% Crl 0.52 to 0.75). Among pharmacological treatments, mineralocorticoid receptor antagonists and irbesartan (MRAs+IRB) had the greatest antihypertensive effect (SBP: WMD = -18.90, 95% Crl -29.20 to -8.55; DBP: WMD = -22.14, 95% Crl -31.81 to -12.50). Mineralocorticoid receptor antagonists did not significantly reduce plasma aldosterone concentration (PAC), consistent with their known feedback-related tendency to increase PAC.ConclusionsThis study showed TADR + RND and MRAs + IRB had best efficacy in surgical and pharmacological treatments, respectively, but 76% of the included studies were conducted in China, which may affect the generalizability of the findings. Therefore, the results need further validation.